Review of the genus Woznessenskia Gorochov, 2002 (Orthoptera: Gryllacrididae) from China - Shi, Fu-Ming; Zhu, Qi-Di; Wang, Hai-Jian (Zootaxa, 2022)
The paper reports four new species of the genus Woznessenskia Gorochov, 2002 and gives supplementary information on Woznessenskia curvicauda (Bey-Bienko, 1962) from China. The specimens examined are deposited in the Museum of Hebei University, Baoding, China.